Pengaruh Media Pembelajaran Joepardy Game terhadap Kemampuan Berpikir Kritis Siswa pada Mata Pelajaran Fiqih - Rahayu, Inka; Khairuddin, Khairuddin (Lembaga Penelitian dan Pengabdian kepada Masyarakat of Universitas Islam Negeri Jurai Siwo Lampung, 2023)
Jeopardy Game is a media designed to emphasize information management for students. Jeopardy Game improves student’s skill to identify and remember information. This study aimed to discover student’s critical thinking skills in grade VIII students at Mts Ar-Riddha Rengas Pulau. This research employed quantitative methods using non-equivalent control group design techniques. Samples of this study are class VIII A as a control class and class VIII B as an experimental class. The researcher provided 5 oral questions that must be answered in writing to measure students’ critical thinking level. Data analysis technique used is the paired sample t-test analysis test. The results showed that students who were taught using the Jeopardy Game had an average critical thinking score of 80.4 in contrast to the Non-Equivalent Control Group had an average had a critical thinking score of 75.3, it showed that there is positive effect of Jeopardy Game for the students’ critical thinking ability. A Sig 2 Tailed 0.000 < 0.05 so that H0 is tolerated and H1 is accepted. This finding concluded that the use of Jeopardy Games affected students’ activities and critical thinking skills in Fiqh at Mts Ar-Riddha Rengas Pulau.